2001
DOI: 10.1021/jm001114o
|View full text |Cite
|
Sign up to set email alerts
|

5‘-O-Alkyl Ethers of N,2-Substituted Adenosine Derivatives:  Partial Agonists for the Adenosine A1 and A3 Receptors

Abstract: New N,5'-di- and N,2,5'-trisubstituted adenosine derivatives were synthesized in good overall yields. Appropriate 5-O-alkyl-substituted ribose moieties were coupled to 6-chloropurine or 2,6-dichloropurine via Vorbrüggen's glycosylation method. Subsequent amination and deprotection of the intermediates yielded compounds 18-35. Binding affinities were determined for rat adenosine A1 and A2A receptors and the human A3 receptor. The ability of compounds 18-35 to inhibit forskolin-induced (10 microM) cyclic AMP (cA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…Most of these analogues are 2-ether substituted adenosine derivatives, which have been previously evaluated at the rat A 1 and A 2A ARs but not at the four human subtypes in a systematic manner [15][16][17][18][19][20]. From previous studies [7,13,21] and in greatly expanded form in the present study, it is clear that the intrinsic efficacy of adenosine derivatives at the A 3 AR is dependent on structural changes at both the N 6 -position and the 2-position. The intrinsic efficacy at the A 2A AR tended to be insensitive to the same structural changes.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Most of these analogues are 2-ether substituted adenosine derivatives, which have been previously evaluated at the rat A 1 and A 2A ARs but not at the four human subtypes in a systematic manner [15][16][17][18][19][20]. From previous studies [7,13,21] and in greatly expanded form in the present study, it is clear that the intrinsic efficacy of adenosine derivatives at the A 3 AR is dependent on structural changes at both the N 6 -position and the 2-position. The intrinsic efficacy at the A 2A AR tended to be insensitive to the same structural changes.…”
Section: Introductionmentioning
confidence: 71%
“…The intrinsic efficacy of adenosine derivatives in activation of the A 3 AR is more variable than at other subtypes [7][8][9][10]. Specific groups placed at the N 6 -position and on the ribose moiety have reduced or completely abolished the ability to activate this receptor, while maintaining high binding affinity.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies it has been demonstrated that the intrinsic efficacy of adenosine derivatives in human A 3 AR activation depended upon both N 6 -and 2-substitutions at the adenine moiety [8][9][10][11][12]. For example, N 6 -substituents consisting of a large cycloalkyl group (>5 carbons) reduced efficacy compared to smaller rings in the activation of the human A 3 AR.…”
Section: Discussionmentioning
confidence: 99%
“…1) was synthesized [14,15,20,21] and compared in binding and functional assays ( Table 1). The set of analogues included nucleosides having a 5′-uronamide modification (1, 2, 8, 9, and 13-16), modification of a hydroxy group either through chiral inversion (3) or through fluorosubstitution (4-9), or a 4′-thio modification (10)(11)(12)(13)(14)(15). 3′-Fluoro (7-9) and 5′-uronamide-4′-thionucleoside (13-15) analogues were reported previously and partially characterized pharmacologically [15].…”
Section: Structures Of Ribose-modified Nucleoside Analoguesmentioning
confidence: 99%
See 1 more Smart Citation